Surface expression of the beta T cell receptor (TCR) chain in the absence of other TCR or CD3 proteins on immature T cells. - Kishi, H (1991)
T cell receptor (TCR) beta genes are rearranged prior to TCR alpha genes. A productively rearranged TCR beta gene suppresses further V beta gene rearrangement. Here we show that in beta TCR transgenic mice the TCR beta-chain can be expressed on the surface of immature CD4-8- thymocytes, but not on mature T cells, in the absence of any other known TCR chain and proteins of the CD3 complex. Analysis by NEPHGE and SDS-PAGE showed that at least some beta TCR exists on the surface as a large disulfide-linked complex with unknown acidic molecules. The introduction of the beta TCR gene into scid mice resulted in the expression of the beta TCR on the cell surface of thymocytes and induced the expression of CD4 and CD8 co-receptors as well as transcription of the alpha TCR locus.